2017
DOI: 10.15298/rusjtheriol.16.1.06
|View full text |Cite
|
Sign up to set email alerts
|

The first data on the infestation of the parti-coloured bat, Vespertilio murinus (Chiroptera, Vespertilionidae), with gamasid mites, Steatonyssus spinosus (Mesostigmata, Gamasina, Macronyssidae)

Abstract: This article presents one of the very few records of a macronyssid mite (Mesostigmata, Gamasina, Macronyssidae) infestation of vesper bats (Chiroptera, Vespertilionidae). It is the first report of the influence of host parameters on the infestation of the parti-coloured bat, Vespertilio murinus, by the mite Steatonyssus spinosus. It has been shown that the infestation varies considerably throughout the host's occupation of summer roosts and the highest infestation was observed in the post-lactation period. Fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Their deutonymphs do not exhibit any adaptations to phoresis, nor have they ever been observed on insects or myriapods. They are also unlikely to be carried by bats, as research on the mites they carry has been fairly extensive, including research on the common noctule analysed in this study, as, so far, their presence has not been observed [44][45][46][47][48]. Consequently, deutonymphs are most likely carried by birds, especially since the specific structure of the barbs allows the deutonymphs to 'hook' onto feathers.…”
Section: Discussionmentioning
confidence: 99%
“…Their deutonymphs do not exhibit any adaptations to phoresis, nor have they ever been observed on insects or myriapods. They are also unlikely to be carried by bats, as research on the mites they carry has been fairly extensive, including research on the common noctule analysed in this study, as, so far, their presence has not been observed [44][45][46][47][48]. Consequently, deutonymphs are most likely carried by birds, especially since the specific structure of the barbs allows the deutonymphs to 'hook' onto feathers.…”
Section: Discussionmentioning
confidence: 99%
“…The family Macronyssidae Oudemans, 1936 has 35 known genera worldwide (Radovsky 2010;Orlova et al 2017;Bassini-Silva et al 2021;Gomes-Almeida and Pepato 2021). The genus Acanthonyssus Yunker and Radovsky, 1966 has two valid species: Acanthonyssus dentipes (Strandtmann and Eads, 1947) and Acanthonyssus proechimys Yunker and Saunders, 1973.…”
Section: Palavras-chave: áCaros Ectoparasitas Proechimys Novo Registromentioning
confidence: 99%
“…Mites of the family Macronyssidae Oudemans, 1936 are primarily ectoparasites of bats, although some genera parasitize reptiles, birds and other mammals (Radovsky 2010). Currently, there are approximately 35 genera and 241 valid species (Radovsky 2010;Orlova et al 2017;Bassini-Silva et al 2021;Gomes-Almeida & Pepato 2021). The recent detection of Ehrlichia spp.…”
mentioning
confidence: 99%